LINGUISTIC MEANING AS A PART OF THE CONCEPTUAL MODEL OF THE WORLD - Maciejczak, Marek (Studia Philosophiae Christianae, 2020)
The paper deals with the concept of the model of the word. It concerns a pre-linguistic stage of language acquisition, descriptive content of proper names and interpretation by means of a conceptual system. The model of the world comprises all aspects of being conscious. It is a system, a unity, a background of our conscious life; perception, language, notions, concepts, are its aspects. The more we know about cognitive processes, functions and structure of the mind, the beer we understand the nature of language; the more we know about language, the better we understand the nature of the mind. Linguistic meaning as it was shown by the studies of language and categories acquisition, has its origin in the aforementioned model. That is why linguistic meanings are not ready-made contents, ideas, semantic entities, etc. but rather systems of procedures that constitute sense of speech acts. The approach to linguistic meaning as a part of an individual conceptual system, a system of information that mirrors cognitive, linguistic and non-verbal experience of an individual, is much of help in understanding efficacy of language, forming of beliefs, convictions, and also introducing new meanings.